Efeito da aplicação de doses de nitrogênio e da cobertura morta sobre a produção de três cultivares de alho - Alves de Menezes Sobrinho , João; Ferreira de Novais , Roberto; Lopes dos Santos, Hélio; Aguiar Sans, Luiz Marcelo (Revista Ceres, 2025)
The objective of the present work was to study the effect of soil mulch and levels of nitrogen on productivity and related characters in three cultivars of garlic. The cultivars ’Amarante’, ’Branco’ and ’Barbado’ were grown at nitrogen (as ammonium sulfate) levels of 0,500 and 1000 kg/ha in the presence and absence of mulch.